Konsep Kompilasi Hukum Ekonomi Syariah Terhadap Gaji Buruh Di Desa Sawah Mudik Kecamatan Ranah Batahan - Roah, Inim; Simanjuntak, Dahliati (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This research examines how the determination of workers' wages in the village of Sawah Mudik is reviewed according to the Compilation of Sharia Economic Law. The research method used is field research with a qualitative approach. Primary data sources, namely primary data sources in this study are male workers, female workers and land owners while secondary data is from books and scientific journals that are considered relevant to this research. data collection techniques with observation, interviews and documentation, with qualitative descriptive data analysis techniques. The results of this study are that the wages given by the employer to farm laborers in Sawah Mudik Village, Ranah Batahan District, West Pasaman Regency, if they work all day are IDR 70,000.00, if the workers are given lunch by the employer and if the workers bring their own lunch, the workers receive a wage of IDR 80,000.00. Meanwhile, the wages that female workers get if they work all day are IDR 50,000.00, if the workers are given lunch by the employer and if the workers bring their own lunch, the workers receive IDR 60,000.00. The wages made by the Sawah Mudik village community are in accordance with the review of the compilation of Sharia economic law if Mu'ajir has made a difference in wages between male and female farm workers on the basis that female farm workers often arrive late, men are more responsible for earning a living for his family and the majority of men do their jobs faster. If the mu'ajir gives a difference in wages between male and female farm workers on the basis of following customs that have become the customs of the local community without considering the above factors even though the type of work and the workload of male and female farm workers are the same. So in Sharia Economic Law it is not allowed because the Koran does not recognize differences between men and women because before Allah men and women have the same degree of position and what distinguishes between men and women is only their faith and piety. So this will be detrimental to farm workers and can cause harm.